A Phase III Randomized, Double-blind, Clinical Trial of an Investigational Hexavalent Vaccine Given at Two, Three, Four and Twelve Months. Issue 2 (February 2017) - Vesikari, Timo; Becker, Thomas; Vertruyen, Andre F.; Poschet, Katleen; Flores, Sheryl A.; Pagnoni, Marco F.; Xu, Jin; Liu, G. Frank; Stek, Jon E.; Boisnard, Florence; Thomas, Stéphane; Ziani, Eddy; et al.
Abstract : Background: Combination vaccines simplify vaccination visits and improve coverage and timeliness. Diphtheria–tetanus toxoids–acellular pertussis 5, hepatitis B, inactivated poliovirus vaccine and Haemophilus influenzae type b (DTaP5–HB–IPV–Hib) is a new investigational, fully liquid, combination vaccine containing a 5-antigen pertussis component and is designed to protect against 6 infectious diseases. Methods: In this multicenter, double-blind, comparator-controlled, phase III study (NCT01341639) conducted in Finland, Germany and Belgium, healthy infants were randomized 1:1 to receive 1 of 2 immunization regimens. The DTaP5–HB–IPV–Hib group received the investigational hexavalent vaccine (DTaP–HB–IPV–Hib) and the Control group received Infanrix-hexa (DTPa3–HBV–IPV/Hib) at 2, 3, 4 and 12 months of age. Both groups received concomitantly Prevnar 13 (PCV13) and Rotateq (RV5) at 2, 3 and 4 months of age and ProqQad (MMRV) at 12 months of age. MMRV was also administered to all study subjects at 13 months of age. Results: A total of 628 subjects in the DTaP5–HB–IPV–Hib group and 622 subjects in the Control group were randomized. In a per-protocol analysis, immune responses to vaccine antigens 1 month after dose 3 and after the toddler dose were noninferior in the DTaP5–HB–IPV–Hib group as compared with the Control group. The DTaP5–HB–IPV–Hib group responses to MMRV given concomitantly at 12 months were all noninferior compared with the Control group. Solicited adverse event rates after any dose, including fever, were similar in both groups. Most adverse events were mild-to-moderate and did not lead to subject withdrawal. Vaccine-related serious adverse events occurred infrequently in the DTaP5–HB–IPV–Hib group (0.3%) and the Control group (0.2%). Conclusions: The safety and immunogenicity of DTaP5–HB–IPV–Hib is comparable to Control when administered in the 2-month, 3-month, 4-month and 12-month schedule. DTaP5–HB–IPV–Hib has the potential to provide a new hexavalent option for pediatric combination vaccines, aligned with recommended immunizations in Europe. Abstract : Supplemental Digital Content is available in the text.